Predicting the drying properties of sludge based on hydrothermal treatment under subcritical conditions. (15th March 2016) - Mäkelä, Mikko; Fraikin, Laurent; Léonard, Angélique; Benavente, Verónica; Fullana, Andrés
Abstract: The effects of hydrothermal treatment on the drying properties of sludge were determined. Sludge was hydrothermally treated at 180–260 °C for 0.5–5 h using NaOH and HCl as additives to influence reaction conditions. Untreated sludge and attained hydrochar samples were then dried under identical conditions with a laboratory microdryer and an X-ray microtomograph was used to follow changes in sample dimensions. The effective moisture diffusivities of sludge and hydrochar samples were determined and the effect of process conditions on respective mean diffusivities evaluated using multiple linear regression. Based on the results the drying time of untreated sludge decreased from approximately 80 min to 37–59 min for sludge hydrochar. Drying of untreated sludge was governed by the falling rate period where drying flux decreased continuously as a function of sludge moisture content due to heat and mass transfer limitations and sample shrinkage. Hydrothermal treatment increased the drying flux of sludge hydrochar and decreased the effect of internal heat and mass transfer limitations and sample shrinkage especially at higher treatment temperatures. The determined effective moisture diffusivities of sludge and hydrochar increased as a function of decreasing moisture content and the mean diffusivity of untreated sludge (8.56·10 −9  m 2  s −1 ) and sludge hydrochar (12.7–27.5·10 −9  m 2  s −1 ) were found statistically different. The attained regression model indicated that treatment temperature governed the mean diffusivity of hydrochar, as the effects of NaOH and HCl were statistically insignificant. The attained results enabled prediction of sludge drying properties through mean moisture diffusivity based on hydrothermal treatment conditions. Graphical abstract: Highlights: Hydrothermal treatment increased drying flux and decreased sludge shrinkage. Effective moisture diffusivity increased as a function of decreasing sample moisture. Treatment temperature controlled the mean diffusivity of sludge hydrochar. Drying properties predicted based on hydrothermal treatment conditions.